Tridiagonal pairs of q-Racah type, the Bockting operator psi, and L-operators for Usubq(L(slsub2)) - Terwilliger, Paul (Ars mathematica contemporanea, 2018)
Opišemo Bocktingov operator ?$ψ$? za tridiagonalni par ?$q$?-Racahovega tipa s pomočjo posebnega ?$L$?-operatorja za algebro kvantnih zank ?$U_q(L(\mathfrak{sl}_2))$?.
Keywords: Bocktingov operator; Leonardov par; tridiagonalen par